Analysis of the Effectiveness of the Literacy-Orientation-Collaboration-Reflection (LOC-R) Learning Model in Science Learning Activities of Islamic Elementary School Students - Iskandar, Suhendra (Jurnal Pijar Mipa, 2024)
Unlike other learning models, the LOC-R learning model focuses on literacy in learning material so that no single learning objective is neglected. However, the learning concept still relies on student-centered learning (SCL). This research examined the effectiveness of the LOC-R learning model (literacy, orientation, collaboration, and reflection) in science learning activities for Madrasah Ibtidaiyah Teacher Education IAIN Sultan Amai Gorontalo students. The research used a learning model focusing only on lecturers' lectures and a learning model concentrating on students' independent presentations as a control group. Three learning materials were selected for the science learning activities, two for the control group (one-way lecture and presentation) and one for the test group, assessed as having the same difficulty level. The success of learning activities is evaluated in two aspects: learning outcomes and student interest in learning. To test the learning outcomes of each group, a pre-test was carried out at the beginning of each learning activity and a post-test at the end of each learning activity for the three groups. Then, the results were analyzed using the N-gain test technique. In addition, a semi-quantitative analysis of students' learning interests was also carried out through questionnaires. The results obtained were that the LOC-R learning model was proven to improve student learning outcomes as seen from the N-gain value of 87.4035%, which was much greater than the control group, where the one-way lecture method only produced an N-gain value of 39.5127% and the presentation method produced an N-gain value of 45.6645%. However, based on the questionnaire given to students who took the LOC-R learning model test, not all showed positive interest, with 50% of students rating it positively, 13.64% rating it neutral, and 36.36% rating it negatively. From this research, researchers can conclude that the LOC-R learning model has proven effective in improving student learning outcomes. However, there is still a need to think about ways to package the learning model innovatively so that it can be popular with all students.